Differences in risk behaviours and HIV/STI prevalence between low-fee and medium-fee female sex workers in three provinces in China. (16th October 2015) - Han, Lifeng; Zhou, Chu; Li, Zhijun; Poon, Adrienne N; Rou, Keming; Fuller, Serena; Li, Yan; Shen, Limei; Kang, Dianmin; Huang, Lu; Liao, Meizhen; Fu, Xiaobing; et al.
Abstract : Objectives: To better understand risk behaviours and factors associated with low-fee female sex workers (FSW) and support HIV/sexually transmitted infections (STI) epidemic control among this key population in China. Methods: A cross-sectional study using convenience sampling to recruit 1487 eligible low-fee and medium-fee FSW was conducted in 2012 in three provinces. The participants were interviewed using a structured questionnaire and tested for HIV-1, herpes simplex virus (HSV)-2 and syphilis antibody. Log-binomial modelling was used to estimate prevalence ratios (PR) and examine factors associated with low-fee sex work. Results: Prevalence of HIV-1, syphilis and HSV-2 antibody positive were 0.5%, 4.8% and 27.8%, respectively. Low-fee FSW were more likely to have HSV-2 infection (adjusted prevalence ratio (APR)=1.3, 95% CI 1.1 to 1.7), but not more likely to have HIV-1 and syphilis infection compared with medium-fee FSW. Compared with medium-fee FSW, low-fee FSW were more likely to be ≥35 years of age (APR=2.1, 95% CI 1.3 to 3.6), engage in sex work ≥6 days/per week (APR=1.7, 95% CI 1.2 to 2.6), have ≥3 clients per day (APR=2.2, 95% CI 1.5 to 3.3), have clients decide condom use (APR=1.6, 95% CI 1.1 to 2.3), fail to persuade clients to use condoms (APR=1.6, 95% CI 1.1 to 2.6), express willingness to have unprotected sex in return for receipt of a higher fee (APR=1.8, 95% CI 1.2 to 2.8), have had genital symptoms in the past year (APR=1.4, 95% CI 1.1 to 1.8) and have migrated from another city. Conclusions: Low-fee FSW in China have unique risks for acquiring HIV/STI, in part due to greater economic pressures. Tailored interventions targeting low-fee FSW and incorporating their prevailing perception of HIV/STI risks and condom use negotiation challenges that they face are urgently needed.